TRADE INTEGRATION BETWEEN ALBANIA AND EUROPEAN UNION A GRAVITY MODEL BASED ANALYSIS - Fetahu, Elvira (European Scientific Journal, ESJ, 2014)
International trade integration of an economy is a stone for a successful economic development of a country. In the context of European Union enlargement there is a specific interest in exploring the regional trade integration of the countries inspiring the involvement in the EU. As a rather successful econometric approach the gravity model has been widely used to infer and predict substantial foreign trade flows between countries more empirically than theoretically. The aim of this study is to examine the potential trade volume between European Union and Albania which is trying to join it in the near future. The focus of Albania is how Albania can integrate to the EU market and gather benefits from this international trade possibility to foster its economic development. Considering the previous agreements bilateral, or involving reciprocity between Albania and EU, as well as the recent status of Albania as the country favored in the international reciprocal economic exchanges, where it is verified a not very happy situation for Albania, the analyze of the situation through the gravity model, gives us some conclusions on how Albania should move in the future in this international trade process to increase its benefits. The new situation coming in the near future, in case Albania gets the status of the candidate country (acceding country), this model can help us find the most weighting variables in the increase of the benefits from the Albania-EU international trade in our favor, in favor of Albania